POLA KONSUMSI IKAN SEGAR OLEH RUMAH TANGGA DI KOTA BANDAR LAMPUNG - Syarif, M. Ryan Afif Marifza; Haryono, Dwi; Situmorang, Suriaty (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
pattern, and factors that influence the consumption in Bandar Lampung City. The data in this research were analyzed descriptively and qualitatively. The locations and 54 respondents of this research were determined purposively, at Sukarame Village, Beringin Raya Village, and Panjang Utara Village, with the total respondents of 20, 19, and 15 households respectively. The results of this research showed that the average of daily fresh fish consumption in Bandar Lampung City was 26.61 grams protein per household. Fresh fish consumption pattern included the kind of the fish was freshwater catfish, the frequency of fresh fish consumption was 4.10-6.00 kg per month; and place to buy fresh fish was traditional markets. Factors that influence the fresh fish consumption in Bandar Lampung City were price of fresh fish, the number of household members and middle economy degree. Key words: consumption pattern, factors, fresh fish consumption